Inovação pública, Govtechs e participação política digital - Zschieschang, Thaís (2023)
The thesis systematizes challenges and potentials of the digital innovation and political participation ecosystem, qualifying the principles of effectiveness and legitimacy of public policies and services. Public participation is categorized in the processes of problem prioritization, ideation, and solution development, as well as their testing, use and evaluation; regardless of the origin of the solution, whether it is internally developed, externally sourced - mainly empowered by govtechs - or combined, representing a new cultural model of management focused on results and the positive and collective generation of value to strengthen management, innovation, and public digitalization agendas, data collection and intelligence, and transparency. Participatory exclusions inherited from analog contexts, as well as new ones seen as results of the digital context, are present with segments of socially subjugated profiles, localities, and vulnerable communities; involving political and technological access, networks, equipment, and digital literacy, relating remote participatory means to the effects of social isolation from 2020 to 2022 with the creation and use of technological solutions. Legal analysis of public procurement and promotion of innovative solutions; market history and investment capacity; and expectations of modernization and technology usage by the government add to the institutional political context and citizen identity, from participatory possibilities with the instrumental use of technology and access to digital political environments, signifying democratic quality and validation of its institutional system. The Analytical Model of Effectiveness and Legitimacy in Public Innovation is constructed from an ecosystem reading and primary data collection with 32 stakeholders representing innovation and solution promoters, public officials and politicians, and solution developers. The model is based on the Theory of Political Consciousness, highlighting links in participatory quality and political motivation for developing solutions to complex socio-environmental, economic, and cultural problems, with an emphasis on the govtech market